Upaya Konservasi Penyu sebagai Penyelamat dari Ancaman Kepunahan dalam Perspektif Islam - Will Helmina, Leony Regina (Es-Syajar:Journal of Islam, Science and Technology Integration, 2024)
Turtle is one of the marine fauna that is protected because its existence is threatened with extinction. The high exploitation of turtles will threaten the sustainability of turtles in the future. Turtles are hunted a lot because of the high selling value of turtle body parts. The uniqueness of the shells on turtles to be used as accessories, until they are preserved for display is a common thing. In addition, the extinction of turtles also occurs because turtles are often trapped in fishing nets and turtles are carried by strong currents to hit coral which causes many turtle carcasses to be found. Through these problems, marine environmentalists find the right solution. To cope with the extinction, turtle breeding centers were built in various coastal areas in Indonesia. Various elements of society work together in efforts to conserve turtles. As a result, there are turtle breeding sites on every coast, for example turtle conservation on Pangumbuhanbeach in West Java, turtle conservation in Bali, and turtle conservation in Banyuwangi. Allah has given the mandate to humans as stated in the Qur'an.